2020
DOI: 10.1093/infdis/jiz567
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plasmid-Encoded H-NS–like Protein on blaNDM-1-Bearing IncX3 Plasmid in Escherichia coli

Abstract: Background This study was performed to assess the role of the histone-like nucleoid-structuring (H-NS)–like protein, carried by blaNDM-1-encoding IncX3-type plasmids, in the dissemination of IncX3 plasmids. Methods The blaNDM-1-encoding IncX3 plasmids were analyzed using southern blot, conjugation, and competition assays. Virulence was evaluated with a Galleria mellonella infection model. An hns-knockout IncX3 plasmid was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…In this study, three strains of bla NDM-5 -positive E. coli were detected in IncX3 plasmid. Genomic sequence analysis showed that the IncX3 plasmid was highly similar to that reported in the Enterobacteriaceae such as E. coli and Klebsiella pneumoniae from human clinic, environment and food animals published in the database [18,19], suggesting that IncX3 plasmid has been widely prevalent.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, three strains of bla NDM-5 -positive E. coli were detected in IncX3 plasmid. Genomic sequence analysis showed that the IncX3 plasmid was highly similar to that reported in the Enterobacteriaceae such as E. coli and Klebsiella pneumoniae from human clinic, environment and food animals published in the database [18,19], suggesting that IncX3 plasmid has been widely prevalent.…”
Section: Discussionsupporting
confidence: 62%
“…plasmids, the absence of a plasmid-encoded H-NS-like protein up-regulates the expression of transfer genes through an uncharacterized pathway, causing a 2.5-fold increase in transfer frequency of IncX3 plasmids (33). Thus, PixR is the first transcriptional activator of transfer genes identified in IncX plasmids, which expands our knowledge of the conjugation of IncX plasmids.…”
Section: Discussionmentioning
confidence: 85%
“…According to a previous method ( Liu et al, 2020 ), overnight cultures of strains carrying pRF14-1, pSC4R, pHS14-2, and its recipient bacteria were diluted 1:1,000 into fresh LB broth and were incubated at 37°C with 200 rpm for 12 h. Growth curves were obtained by measuring the optical density of cultures at 620 nm every hour by Multiskan FC (Thermo Fisher Scientific). All experiments were conducted in triplicate and repeated three times independently, and the average values were used to estimate growth parameters.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that some plasmids also have genes encoding H-NS family proteins, and the deletion of hns decreases the fitness of host bacteria ( Doyle et al, 2007 ), indicating that H-NS is likely to mediate the fitness cost of plasmids. A recent study showed that H-NS plays an important role in the dissemination of bla NDM– 1 -bearing IncX3 Plasmid in Escherichia coli by regulating the expression of plasmid-related genes ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%